Meningkatkan Penjualan Pada Produk TWOCFOOD Melalui Display Diaplikasi Bloger - Shillfia Widya Putri; DEWI LAKSANA JANNATY; Miranda; Wulandari; Novadilastri, Novadilastri; Sularno, Sularno (CV. ITTC INDONESIA, 2023)
This basic learning project explains how to increase sales of Twocfood brand Frozen Food MSME products by displaying their products on blogger programs. SMEs usually sell either through offline sales or through a system in grocery stores, supermarkets. so that the development of the product is slow, in terms of sales it is also limited to a certain area, so this basic training aims to increase sales in Twocfood MSME companies. through the web system in the blogger application from product introduction to ordering. Registering products on Blogger involves several steps, starting with information gathering, product analysis, and business evaluation of Twocfood. strategies that are then applied online when selling through the blogger program. Before creating an MSME blogger, an analysis of consumer behavior and online store shopping habits was first conducted. This step allowed Twocfood to customize its content and marketing strategies to communicate effectively with target consumers. In addition, this research emphasizes the importance of creating valuable and engaging content that meets the interests, needs and wants of visitors/consumers. In addition, the proposed strategy also includes search engine optimization techniques to ensure better visibility and discoverability of Twocfood's blog. By optimizing keywords, content description fields, and other page elements, Twocfood can improve its search engine rankings. Keywords:MSME Product Display, Blogger Application, sales.